Attenuation of Positive Valence in Ratings of Affective Sounds by Tinnitus Patients. (December 2018) - Szibor, Annett; Lehtimäki, Jarmo; Ylikoski, Jukka; Aarnisalo, Antti A.; Mäkitie, Antti; Hyvärinen, Petteri
Affective processing appears to be altered in tinnitus, and the condition is to a large extent characterized by the emotional reaction to the phantom sound. Psychophysiological models of tinnitus and supporting brain imaging studies have suggested a role for the limbic system in the emergence and maintenance of tinnitus. It is not clear whether the tinnitus-related changes in these systems are specific for tinnitus only, or whether they affect emotional processing more generally. In this study, we aimed to quantify possible deviations in affective processing in tinnitus patients by behavioral and physiological measures. Tinnitus patients rated the valence and arousal of sounds from the International Affective Digitized Sounds database. Sounds were chosen based on the normative valence ratings, that is, negative, neutral, or positive. The individual autonomic response was measured simultaneously with pupillometry. We found that the subjective ratings of the sounds by tinnitus patients differed significantly from the normative ratings. The difference was most pronounced for positive sounds, where sounds were rated lower on both valence and arousal scales. Negative and neutral sounds were rated differently only for arousal. Pupil measurements paralleled the behavioral results, showing a dampened response to positive sounds. Taken together, our findings suggest that affective processing is altered in tinnitus patients. The results are in line with earlier studies in depressed patients, which have provided evidence in favor of the so-called positive attenuation hypothesis of depression. Thus, the current results highlight the close link between tinnitus and depression.